Funciones desempeñadas como asesor de negocios en la Coopac NSR - Ag. Huamachuco - Gastañadui Ulloa, José Noe (2018)
This report, briefly describes the author's experience from September 2013 to the present within the Savings and Credit Cooperative Nuestra Señora del Rosario Ltda. No. 222 - Ag. Huamachuco as a graduate of the Faculty of Economics, academic school Professional of Administration, of the National University of Trujillo. The Savings and Credit Cooperative Nuestra Señora del Rosario Ltda. No. 222, has been the birthplace and home of thousands of competent professionals, thanks to the combination of the educational method taught in our classrooms, coupled with the requirement that as a leading Cooperative, is printed in your collaborators. The economic events that have taken place in recent years, and nowadays, have transformed the demands and skills that the market now demands. Globalization, technology and a world open to more and more possibilities have generated today, that there are few or almost no differences between the acquisition of a certain product and / or service in the market. Thus arises the need to potentiate, not only the purchase and sale of a product and / or service, but to endow this process with the greatest amount of tools with the purpose of making an intangible and powerful difference, providing a satisfactory experience and commit the customer to return or buy back every time they have or are born in their environment any need. In this sense, this report draws up the functions, contributions, criticisms and recommendations of the author in order to contribute to the development and research of future young graduates, in addition to proposing some options or alternative development in the education of future students.